2021
DOI: 10.1007/s11302-021-09766-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intranasal guanosine administration on brain function in a rat model of ischemic stroke

Abstract: Ischemic stroke is a major cause of morbidity and mortality worldwide and only few affected patients are able to receive treatment, especially in developing countries. Detailed pathophysiology of brain ischemia has been extensively studied in order to discover new treatments with a broad therapeutic window and that are accessible to patients worldwide. The nucleoside guanosine (Guo) has been shown to have neuroprotective effects in animal models of brain diseases, including ischemic stroke. In a rat model of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 77 publications
0
17
0
Order By: Relevance
“…To our knowledge, no studies have reported any major side effects of exogenously administered Guo in in vivo models [74,163,165]. Guo administered i.p did not impair renal function.…”
Section: Safety and Pharmacokinetics Of Exogenous Guanosine In Rodent Models-implications In Ischemic Strokementioning
confidence: 77%
See 4 more Smart Citations
“…To our knowledge, no studies have reported any major side effects of exogenously administered Guo in in vivo models [74,163,165]. Guo administered i.p did not impair renal function.…”
Section: Safety and Pharmacokinetics Of Exogenous Guanosine In Rodent Models-implications In Ischemic Strokementioning
confidence: 77%
“…In the rat ischemia model (thermocoagulation of pial vessels), IN administration of Guo was able to attenuate neurological deficits when administered as late as 3 h after ischemia onset. Contrarily, using the systemic route, Guo-elicited neuroprotection could only be observed when administered immediately after stroke induction [163].…”
Section: Safety and Pharmacokinetics Of Exogenous Guanosine In Rodent Models-implications In Ischemic Strokementioning
confidence: 99%
See 3 more Smart Citations